The Impact of Perceived Usefulness, Convenience, and Perceived Augmentation on Purchase Intention: A Study of Virtual Try-On for Cosmetic Products - Fitri Hasibuan, Desya Andini (Journal The Winners, 2025)
The COVID-19 pandemic has accelerated the shift toward online shopping, especially for cosmetic products. However, a major challenge remains: consumers cannot physically try on products before purchase. Augmented reality (AR) and virtual try-on features address this issue by allowing consumers to virtually try on cosmetic products, creating a more realistic shopping experience. This research analyzes the factors that affect the adoption of AR in the Indonesian cosmetics market, focusing on perceived usefulness, convenience, and perceived augmentation as determinants of customer engagement and purchase intention. Based on the Technology Acceptance Model (TAM) and the Theory of Interactive Media Effects (TIME), a conceptual framework was developed to analyze these relationships. Quantitative methods were applied using convenience sampling and snowball sampling, with data collected from 350 respondents who had prior experience using virtual try-on for cosmetics through mobile commerce. Structural Equation Modeling (SEM) with SmartPLS was used to test the proposed relationships between the variables. The results indicate that perceived usefulness, convenience, and perceived augmentation have a positive effect on customer engagement and purchase intention. Additionally, customer engagement was found to be a significant mediator between the three factors and purchase intention, highlighting its crucial role in driving consumer purchase intention.